Validity and Reliability of the 4TMC Diagnostic Test Instrument Based on Chemical Representation on Chemical Bonding Material to Detect Student Misconceptions - Almira, Sabrina Angeli; Alya Aqilah Zahra; Novita, Dian (Universitas Negeri Surabaya, 2025)
This study aims to produce a valid four-tier multiple-choice diagnostic test instrument based on validity and reliability and to detect students misconceptions the concept of chemical bonds using the developed instrument. The research design used in this development uses research and development (R&D) of Thiagarajan's modified 4D model consisting of four stages, namely the stages (define, design, develop, disseminate). Based on the results of the study, it can be concluded that (1) the validity of the instrument who reviewed from the content and construct aspects has a score mode of 4, (2) the Cronbach Alpha value is 0.825 which means it is reliable and (3) the misconception profile owned by students for each sub-material of ionic bonds is 33%, metal bonds are 40% and covalent bonds are 51.51%. Based on the results of validity and reliability, the diagnostic test instrument developed can be declared valid for use.